Do IPO Hot and Cold Markets Exist at the Indonesia Stock Exchange? - Doni S. Warganegara; Dezie L. Warganegara (Bina Nusantara University, 2014)
This study focuses on IPO Initial Returns in Hot and Cold IPO Markets at the Indonesia Stock Exchange (IDX) between the period of 2001 and 2005. This study uses a regression analysis where the first day IPO stock return is the dependent variable and a dummy variable that represents Hot and Cold IPO Markets is the main independent variabel. It is found that Hot and Cold Markets do exist at the IDX. More importantly, it is found that the difference in IPO Initial Returns between Hot and Cold Markets while controlling for other factors is 36.8%. The Investment Sentiment Hypothesis has been found to explain the existence of Hot and Cold Markets. The hypothesis implies that jumps in IPO Initial Returns during Hot Markets are due to the increase in the first day closing prices which are higher than the increase in the offering prices. The Monopsony Power Hypothesis and information spillovers across IPOs respectively may also provide alternative explanations to the phenomenon. Investment banker community in a small economy learns information from each other and, thus, has full information on the number of firms that will go public in the following period. Consequently, investment bankers have a high bargaining power of investment bankers in lowering the offering prices.